Prevalence and Risk Factors of Knee Osteoarthritis: A Cross-Sectional Study in Palembang, Indonesia - Vanessa Stepania; Nur Rachmat Lubis; Ramadhan Ananditia Putra (HM Publisher, 2025)
Osteoarthritis (OA) is a prevalent degenerative joint disease causing pain, disability, and decreased quality of life. This study aimed to investigate the prevalence and risk factors associated with knee OA in Palembang, Indonesia. A cross-sectional study was conducted using secondary data from medical records of patients diagnosed with knee OA at Dr. Mohammad Hoesin General Hospital in Palembang during 2023. Patients aged ≥ 55 years with primary knee OA were included, while those with secondary knee OA or cerebrovascular disease were excluded. Data on sociodemographics, clinical characteristics, and comorbidities were collected. Univariate analysis and correlation tests were performed to assess the association between risk factors and knee OA. A total of 133 patients with knee OA were included. The majority were female (82%), aged 55-65 years (51.1%), and housewives (48.1%). Bilateral knee involvement was observed in 73.7% of patients. Overweight (35.3%) was the most common BMI category. Hypertension was the most prevalent comorbidity (61.7%), followed by diabetes mellitus (19.5%) and dyslipidemia (19.5%). Correlation analysis showed a significant positive correlation between knee OA and age, female gender, and BMI. In conclusion, knee OA in Palembang is more prevalent in middle-aged women, particularly housewives. Overweight and hypertension are significant risk factors associated with knee OA. These findings underscore the need for targeted preventive strategies and public health interventions to address these modifiable risk factors.